A Distributed and Cooperative Environment for Computer Algebra. - Dalmas, Stephane (Journal of symbolic computation.)
In this paper, we describe theCentral Control, a software component that enables several symbolic systems to cooperate and exchange data. The Central Control has been designed to be the kernel of an environment for scientific computations which can offer a common and concurrent access to several tools needed by the scientist and the engineer: general purpose and specialized computer algebra systems, visualization tools, links with numerical libraries and tools to manipulate numerical programsetc. The user can interact with the Central Control through one or more (graphical) user interfaces. The Central Control achieves its goals by requiring as little as possible from the tools and by using a particular programming language to provide a unified view for the objects and the operations performed by the connected tools. The Central Control will be used as the basis of theComprehensive Solverthat will provide common access to all the programs developed within theImage project. We give a simple example of an actual use of the Central Control for computing primary decompositions of ideals.